DIGITAL ECONOMY AS A DRIVER OF INDUSTRIAL DEVELOPMENT (Marketing Journal, 2026)
AbstractThe article examined the expanding role of the digital economy in strengtheningproduction efficiency within industrial enterprises of the Republic of Uzbekistan. Thestudy traced the progressive trajectory of digital economic development from 2018 to2023, identified key institutional and infrastructural achievements that accelerateddigital transformation, and assessed the promising opportunities for broader adoptionof digital technologies across productive sectors. The analysis demonstrated aconsistent upward trend in the contribution of the digital economy to aggregate outputand documented substantial improvements in ICT infrastructure, e-governancecapacity, and enterprise-level digital adoption. The findings confirmed that Uzbekistanhas established a robust institutional foundation for sustained digital economic growth,with expanding internet access, a strengthening regulatory environment, and anincreasingly digitally skilled workforce positioning the country favorably for continuedadvancement.Keywords: digital economy, industrial enterprises, production efficiency, ICTdevelopment, e-governance, Uzbekistan